IDENTIFICATION OF THE MODEL OF SOCIALLY-ORIENTED INNOVATIVE ENTERPRISE: THEORY AND PRACTICE - Olga A. Boris; Larisa I. Gorbenko; Elena F. Bobrova (Вестник Северо-Кавказского федерального университета)
Under the proposed evaluation system type of socio-oriented innovative company calculated the individual evaluation criteria and concluded that the effectiveness of existing enterprises studied holistic management models.